2012
DOI: 10.1038/emboj.2012.31
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol loss during glutamate-mediated excitotoxicity

Abstract: The deregulation of brain cholesterol metabolism is typical in acute neuronal injury (such as stroke, brain trauma and epileptic seizures) and chronic neurodegenerative diseases (Alzheimer's disease). Since both conditions are characterized by excessive stimulation of glutamate receptors, we have here investigated to which extent excitatory neurotransmission plays a role in brain cholesterol homeostasis. We show that a short (30 min) stimulation of glutamatergic neurotransmission induces a small but significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
68
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(78 citation statements)
references
References 57 publications
8
68
0
Order By: Relevance
“…Endogenous 24S-HC may be elevated by excitatory synaptic transmission [2729]. Hippocampal cultures exhibit age-related, activity-dependent cholesterol loss that involves reactive oxygen species, CYP46A1 mobilization [27, 28], and elevated 24S-HC in culture medium [29].…”
Section: Discussionmentioning
confidence: 99%
“…Endogenous 24S-HC may be elevated by excitatory synaptic transmission [2729]. Hippocampal cultures exhibit age-related, activity-dependent cholesterol loss that involves reactive oxygen species, CYP46A1 mobilization [27, 28], and elevated 24S-HC in culture medium [29].…”
Section: Discussionmentioning
confidence: 99%
“…56 Changes in cholesterol pathways and in apoE expression have been also associated to NMDA-mediated excitotoxicity. [57][58][59] Of note, 24OHC is a potent and specific modulator of NMDA receptors. 60 Although cholesterol homeostasis has been reported to contribute to enhanced excitotoxicity in HD, 61 however, further studies are needed to address this relationship.…”
Section: Discussionmentioning
confidence: 99%
“…Acute cholesterol depletion by cyclodextrin treatment results in altered membrane properties that can affect synaptic transmission in Purkinje cells and wildtype hippocampal neurons [57,58]. On the other hand, Sodero and coworkers have suggested that a sudden rise in excitatory neurotransmission activate CYP46A1-dependent mild cholesterol loss mechanisms to protect themselves from neuronal death [59]. Since CYP46A1 activity produces 24OHC, one may speculate that the CYP46A1-sGTPases-LXR axis in neurons is an additional layer of the cell's cholesterol quality control, impairing cholesterol reduction to levels that may affect synaptic transmission.…”
Section: Discussionmentioning
confidence: 99%